Evaluation of dexmedetomidine in combination with sufentanil or butorphanol for postoperative analgesia in patients undergoing laparoscopic resection of gastrointestinal tumors: A quasi-experimental trial - Zhang, Xue-Kang (Medicine (Baltimore), 2016)
The aim of this study was to evaluate the efficacy of dexmedetomidine in combination with sufentanil or butorphanol for postoperative analgesia in patients undergoing laparoscopic resection of a gastrointestinal tumor. This quasi-experimental trial was conducted in Nanchang, China, from January 2014 to December 2015. Eighty patients (age 27–70 years, American Society of Anesthesiologists physical status I–II) undergoing laparoscopic resection of a gastrointestinal tumor were randomized into 4 groups and offered intravenous patient-controlled analgesia for pain control after surgery. The patients received sufentanil 2.0 μg/kg in combination with dexmedetomidine 1.5 μg/kg (group S(1)) or 2.0 μg/kg (group S(2)), or butorphanol 0.15 mg/kg in combination with dexmedetomidine 1.5 0 μg/kg (group N(1)) or 2.0 μg/kg (group N(2)). Oxygen saturation, mean arterial pressure (MAP), heart rate, visual analog scale score, and Ramsay sedation score were recorded at enrollment (T(0)), at extubation (T(1)), and 4 (T(2)), 8 (T(3)), 12 (T(4)), 24 (T(5)), and 48 (T(6)) hours thereafter. Side effects and satisfaction scores were evaluated after surgery. MAP increased in all groups at T(1) but not significantly so when compared with T(0). Heart rate decreased significantly in group S(2) when compared with the other groups at T(1)–T(5) (P < 0.05). MAP decreased significantly in group S(2) when compared with group S(1) at T(4)–T(6) (P < 0.05). MAP increased significantly in group N(1) when compared with group N(2) at T(4)–T(5) (P < 0.05). There was a statistically significant decrease in mean visual analog scale score in group S(2) when compared with group S(1) at T(2) (P < 0.05) and group N(2) at T(1)–T(2) (P < 0.05). Two patients in group S(1) had vomiting. There were no reports of drowsiness, respiratory depression, or other complications. The satisfaction score was higher in group S(2) than in the other groups. Dexmedetomidine in combination with sufentanil or butorphanol can be used safely and effectively for postoperative analgesia in patients undergoing laparoscopic resection of a gastrointestinal tumor. The combination of dexmedetomidine 2.0 μg/kg and sufentanil is particularly beneficial in these patients.